In vitro microcosm of co-cultured bacteria for the removal of hexavalent Cr and tannic acid: A mechanistic approach to study the impact of operational parameters - Prachi Chaudhary; Vikas Beniwal; Ahmad Umar; Raman Kumar; Priyanka Sharma; Anil Kumar; Yas Al-Hadeethi; Vinod Chhokar (Ecotoxicology and Environmental Safety, 2021)
Industrial wastes, for instance, tannery wastes are rich soups of resistant and bioremediation-potent bacteria. In the present work, Chromium (Cr) and tannic acid (TA) resistance bacterial strains were isolated from tannery effluent and identified as Bacillus subtilis (MCC 3275) and Bacillus safensis (MCC 3283) based on its 16S Ribosomal RNA homology. Hexavalent Cr is highly toxic and mutagenic due to its high mobility and reactivity. Whereas, TA is known to inhibit enzyme activity, substrate deprivation, and interaction with membranes and matrix-metal ions. The developed In vitro co-cultured microcosm of B. subtilis and B. safensis was able to remove Cr(VI) up to 95% and TA up to 23%. The bacteria cultures separately were able to degrade Cr(VI) to 88% by B. subtilis and 91% by B. safensis and TA up to 27%. Plackett Burman design (PBD) followed by Response surface methodology (RSM) was applied for the optimization of physio-chemical parameters. The optimized conditions for co-culture development were recorded as K2HPO4 = 0.2 g/L, MgSO4 = 0.2 g/L, NH4Cl = 0.5 g/L, glucose – 0.2 g/L, TA – 5%, Cr = 200 ppm, incubation period of 96 h, agitation speed of 110 rpm, pH = 5.0, temperature= 30 °C and inoculum size = 3%. Scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) revealed the thorough mechanism of cellular uptake followed by degradation of Cr(VI) and TA. The efficiency of co-culture for other heavy metals was observed as follows: Zn 65%, Pb 63%, Cd 65%, and Ni 65%. Bioremediation using bacteria is an economical and environmentally better alternative to conventional remediation methods. The isolated bacteria are useful in the effluent treatment of tannery or related industries and in metal recovery in mining processes.